The effect of assist gas on the surface roughness for carbon dioxide laser cutting process - Muhammad Zaid, Mohamad Mohtar (2012)
This study focuses on the effect of assist gases on the surface roughness for Carbon Dioxide (CO2) laser cutting process. The analysis of the surface roughness has been determined by Surfcom 130A surface roughness tester which it place in laboratory. The material used for this experiment is acrylic sheet with 2.5 mm thickness. In this process the cut quality is very important. The parameters in laser cutting are cutting speed, keft width, laser power, chemistry of gas, nozzle exit parameter, nozzle design, thickness of the specimen and surface quality. In oxygen assist laser cutting, the gas plays two roles, one is to generated additional thermal energy during penetration and second role is to supply the shear force to the gas boundary to eject the molten metal formed during the cutting process. However, for this study, two parameters are selected. There are type of assist gas and gas pressure. Finally, the result show that the no assist gas with the lower pressure bars at certain speed is better quality on surface roughness cutting.